ISOLASI DAN IDENTIFIKASI SENYAWA KIMIA AKTIF KULIT BATANG KERSEN TERHADAP ARTEMIA SALINA - Muhammad Walid; Partomuan Simanjuntak; Ahmad Darmawan (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
Kersen (Muntingia calabura L.) has been widely used by Indonesian people to cure many diseases such as cancer, diabetes, and antioxidant, antiplateletes, and hepatoprotector. The aim of this research is to discover chemical structure of compounds contained in barks of Kersen (Muntingia calabura L.) based on their toxicity by BSLT (Brine Shrimp Lethality Test) method. Barks of Kersen (Muntingia calabura L.) were macerated by 96% ethanol followed by partition with n-hexane and ethyl acetate successively to give n-hexane, ethyl acetate and water extracts. Ethyl acetate extract which showed highest toxicity (LD50 = 29.00 ppm) was purified by column chromatography using SiO2 with eluents (i). n-hexane - ethyl acetate = 20 : 1 1 : 1; (ii). n-hexane - ethyl acetate = 5 : 1 to give fraction 4.4.5 as pure isolated compound. Identification was done based on interpretation of infra red spectrophotometry (FT-IR) and liquid chromatography-mass spectra (LC-MS) data, and supported by references investigation. Finally, we were predicted fraction 4.4.5. as 5-(7,8-dimethoxy-3,4-dihydro-2H-1benzopyran-2-yl)-2,3-dimethoxyphenol with LC50 = 5.76 ppmKeywords: Hypoglycemic, Diabetes Mellitus, Momordica charantia, Apium graveolens L.